The Relationship between Workload and the Level of Occupational Health and Safety Awareness of Nurses at RSU Muhammadiyah Lumajang - Lestari, Dini Ayu; Salam, Ainul Yaqin; Isnawati, Iin Aini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
their duties to address patients' health problems 24 hours a day continuously. These conditions lead to a decrease in nurses' vigilance in implementing health and safety at work. The research design used was correlational analytic, using a cross-sectional approach. The population in this study was all nurses working at Muhammadiyah Lumajang Hospital, which is 30 nurses, using a total sampling technique. To determine the relationship between the two variables. Spearman rank statistical test with a significance level of 0.05. The results obtained. Almost all respondents experienced a moderate workload (70%), and almost all respondents experienced a moderate level of awareness (86.6%). After the Spearman Rank statistical test was carried out, the results of the Sig value were obtained. (2-tailed) the results of a significant level of 0.004 < 0.05, so H0 was rejected and H1 was accepted, meaning there is a relationship between workload and the level of occupational safety and health awareness among nurses at Muhammadiyah Lumajang General Hospital with the level of closeness of the relationship showing the results of the value 0.508 strong category. It is hoped that Muhammadiyah Hospital will meet the ideal number of nurses, adequate facilities and infrastructure, and health insurance for healthcare workers in the future.